Influence of polarization, reorientation, and coupling of dipole on electrocaloric effect in ferroelectrics. Issue 3 (6th November 2019) - Chen, Yong; Chen, Ye; Du, Yike; Liu, Kanghui; Qin, Lu; Jiang, Chaobin; Cao, Wanqiang; Zhao, Jiang; Wang, Wenfeng
Abstract: Electrocaloric effects due to entropy change and dipole coupling upon electric field in second‐order phase transition (tetragonal‐cubic) ferroelectrics are investigated by a three‐dimensional Devonshire's theory and statistic method. In diabatic condition, increase in vibration entropy to heat the ferroelectric is due to decreases in polarization entropy and configuration entropy of dipole reorientation in the specific directions. Coupling effect originated from the reorientation of dipoles accompany with electric hysteresis loop happens in the nearest neighbor dipoles parallel to electric field direction. Numerical simulations exhibit that polarization effect causes electrocaloric peak at the Curie's temperature independent of electric field, reorientation effect of dipole causes a shift of electrocaloric peak to high temperature with electric field, and coupling effect between dipoles gives rise to increase in electrocaloric effect with decreasing temperature. A method to predetermine the excellent electrocaloric effect of ferroelectrics from dielectric and/or polarization experimental results is proposed.